Father’s social and economic position has strongest impact on age at menarche in girls from Central India - Kosińska, Magdalena; Liczbińska, Grażyna; Gautam, Rajesh K.; Dubey, Pragya; Ahirwar, Ajay Kumar; Chaurasia, Anurag (Anthropological Review, 2019)
We assessed the impact of socio-economic factors on age at menarche among the adolescent female population from the state of Madhya Pradesh, Central India. Records such as date of birth, chronological age, caste affiliation, size of place of residence, parents’ level of education and occupation, number of siblings, body height and weight, and age at menarche were collected for 330 students of A Central University, Sagar. The impact of socio-economic factors on age at menarche was analysed using analysis of variance. To establish the probability of menarche occurrence at a given age, time-to-event analysis was carried out using Kaplan-Meier curves and the log-rank test for curve comparison. The association between probability of attaining menarche and the independent variables was investigated using Cox proportional-hazard model. ANOVA and the Kaplan-Meier curves showed statistically significant differences in age at menarche according to size of the place of residence, number of siblings, parental level of education, father’s occupation and females’ BMI. The Cox proportional hazard model revealed that father’s occupation was the strongest factor affecting age at menarche among all SES characteristics under study. Irrespective of rapid economic progress over the past few decades, Indian society is still patriarchal with societal male dominance. This translates into participation of fewer women in the paid workforce and labour market, their lower wage rates and smaller contribution to the household budget compared to their male counterparts.